Time Synchronization in Wireless Sensor Networks Using Max and Average Consensus Protocol. (28th March 2013) - Dengchang, Zhao; Zhulin, An; Yongjun, Xu
This paper proposes a novel distributed time synchronization scheme for wireless sensor networks, which uses max consensus to compensate for clock drift and average consensus to compensate for clock offset. The main idea is to achieve a global synchronization just using local information. The proposed protocol has the advantage of being totally distributed, asynchronous, and robust to packet drop and sensor node failure. Finally, the protocol has been implemented in MATLAB. Through several simulations, we can see that this protocol can reduce clock error to ±10 ticks, adapt to dynamic topology, and be suitable to large-scale applications.